Desain Dermaga Apung Sebagai Sarana Penunjang Kegiatan Ekonomi Nelayan Di Desa Aeng Sareh - Muhammad Haris Afifuddin; Arief Syarifuddin; Anauta Lungiding Angga Risdianto; Qusyairi Lubis (Institut Teknologi dan Bisnis Semarang, 2023)
The dock is a ship mooring facility to support the sustainability of water transportation (Irwan, 2019). Current developments in many docks use floating docks, where the dock is like a pontoon made of steel or concrete boxes and can float according to changes in water level (Utomo, 2018). Many fishermen in the Sampang Regency area moor at docks made of bamboo on the shoulders of rivers and there are also boats moored around the coast. The condition of the bamboo pier on the river is not very suitable because if the river water recedes it will affect when fishermen are loading and unloading. This problem makes researchers want to make the main object to be able to create design training for young fishermen that is appropriate to the conditions of the river in Aeng Sareh Village, which is often used by fishermen to moor their boats. Researchers offer designs to fishermen in Aeng Sareh Village which will later be used for development.